Association of Family History and Physical Activity with Hypertension in Pre-Elderly Adults - Suprapto Suprapto; Nurafriani Nurafriani; Sitti Nurbaya (Edukasi Ilmiah Indonesia, 2025)
Introduction: Hypertension remains a major public health problem globally, particularly among pre-elderly adults (aged 45–59 years), who are at increased risk of developing cardiovascular disease. Both genetic predisposition and lifestyle factors, such as physical activity, play crucial roles in determining hypertension risk. Understanding how family history interacts with physical activity can provide valuable insights for prevention strategies among this population. Methods: This cross-sectional study aimed to analyze the association between family history of hypertension and physical activity with the prevalence of hypertension in pre-elderly adults. A total of 240 respondents aged 45–59 years were selected using stratified random sampling from community health centers. Data on blood pressure were collected through standardized sphygmomanometer measurements. Family history was determined based on self-reported parental or sibling hypertension. Physical activity level was assessed using the International Physical Activity Questionnaire (IPAQ) and categorized as low, moderate, or high. Data were analyzed using chi-square tests and multivariate logistic regression to estimate adjusted odds ratios (AOR) with 95% confidence intervals (CI). Results: The prevalence of hypertension among respondents was 37.5%. A significant association was found between family history and hypertension (p < 0.001), with individuals having a positive family history showing 3.2 times higher odds of hypertension (AOR = 3.24; 95% CI: 1.85–5.68). Physical activity also demonstrated a significant inverse association (p = 0.002), where participants with high activity levels had a 56% lower risk of hypertension compared to those with low activity (AOR = 0.44; 95% CI: 0.25–0.78). Interaction analysis indicated that physically active individuals with a family history still had a reduced risk compared to inactive counterparts. Conclusion: Family history of hypertension and physical activity were significantly associated with hypertension among pre-elderly adults. A positive family history increases the risk, while regular physical activity offers a protective effect. Health promotion programs targeting lifestyle modification and routine blood pressure screening are recommended to prevent early onset of hypertension in this age group.